Thymic Epithelium Abnormalities in DiGeorge and Down Syndrome Patients Contribute to Dysregulation in T Cell Development - Marcovecchio, Genni Enza; Bortolomai, Ileana; Ferrua, Francesca; Fontana, Elena; Imberti, Luisa; Conforti, Erika; Amodio, Donato; Bergante, Sonia; Macchiarulo, Giulia; D'Oria, Veronica; Conti, Francesca; Di Cesare, Silvia; et al. (Frontiers in Immunology, 2019)
The thymus plays a fundamental role in establishing and maintaining central and peripheral tolerance and defects in thymic architecture or AIRE expression result in the development of autoreactive lymphocytes. Patients with partial DiGeorge Syndrome (DGS) and Down Syndrome (DS) present alterations in size and architecture of the thymus and higher risk to develop autoimmunity. We sought to evaluate thymic architecture and thymocyte development in DGS and DS patients and to determine the extent to which thymic defects result in immune dysregulation and T cell homeostasis perturbation in these patients. Thymi from pediatric patients and age-matched controls were obtained to evaluate cortex and medullary compartments, AIRE expression and thymocyte development. In the same patients we also characterized immunophenotype of peripheral T cells. Phenotypic and functional characterization of thymic and peripheral regulatory T (Treg) cells was finally assessed. Histologic analysis revealed peculiar alterations in thymic medulla size and maturation in DGS and DS patients. Perturbed distribution of thymocytes and altered thymic output was also observed. DGS patients showed lower mature CD4+ and CD8+ T cell frequency, associated with reduced proportion and function of Tregs both in thymus and peripheral blood. DS patients showed increased frequency of single positive (SP) thymocytes and thymic Treg cells. However, Tregs isolated both from thymus and peripheral blood of DS patients showed reduced suppressive ability. Our results provide novel insights on thymic defects associated with DGS and DS and their impact on peripheral immune dysregulation. Indeed, thymic abnormalities and defect in thymocyte development, in particular in Treg cell number and function could contribute in the pathogenesis of the immunodysregulation present in partial DGS and in DS patients.